Pengaruh Aplikasi Biochar Tempurung Kelapa dan Pupuk Anorganik terhadap Serapan N P K dan Hasil Tanaman Jagung Manis pada Tanah Gambut - Yupita, Anyon; Hayati, Rita; Hazriani, Rini (Fakultas Pertanian Universitas Tanjungpura, 2023)
Maize (Zea may ssaccharata) is the horticulture in demand current society this. Limited avalability of land productive agriculture causes agricultural development, especially maize plant using peat soil media. Peat soil are low acidity, and nutrient content macro N, P, K available to plant also low. Attempts made for increasing the productivity of peat soils is by giving biochar and proper fertilization. Provision of biochar and inorganic fertilizer in addition to being a source of nutrients for plants, can also improve the physical, chemical and biological properties of the soil. This study aims to determine the influence of the application of coconut shell biochar and inorganic fertilizers on N P K nutrient uptake and maize crop yields. Research using Complete Random Design (CRD) factorial consists of two factors treatment and three replications. The first factor, namely coconut shell biochar which consist of 3 levels. The second factor, namely inorganic fertilizer consisting of 3 levels so there are 27 experimental units consisting of 2 sets of plants. Based on the results of variance, interaction of coconut shell biochar administration and inorganic fertilizer no significantly influence on all treatments. Whereas the administration of coconut shell biochar has no significant influence on soil pH, K uptake and cob weight, but significantly affected the wet weight, dray weight, N uptake and K uptake. Inorganik fertilizer has no significant influence on soil pH, wet weight, dry weight, N uptake and cob weight, but has a significant influence on P uptake and K uptake. The best cob weight is at A1B3 treatment (biochar coconut shell 55 gram/polybag + inorganic fertilizer 5,1 gram/polybag).